Analysis of Game-Based Learning Models in the Motor Development Students 12th Grade Vocational High School in Surakarta - Karim, Rifa'i Abdul; Basori, Basori; Kurniasari, Kurniasari (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2024)
This research is undermined by the need to understand the impact of Game-Based Learning (GBL) models on the motor development of 12th grade RPL Vocational High School in Surakarta. There is an analysis of the gaps associated with the application of GBL in the context of vocational education. The problem formula of this study covers the extent to which the game-based learning model contributes positively to the motor development of 12th grade students. The research method applied is qualitative, with qualitatively descriptive techniques involving the investigation of the motor development of the learners in the application of Game-Based Learning. Data collection on this research uses observation and interview. The participants in this study were 12th grade RPL A pupils and one of RPL Vocational High School teacher in Surakarta. There are four games that are followed by the pupils: Crossword, Matching Pictures, Guess Letters, and Snake Stairs, which discuss Mobile Device Web Programming subjects related to Android Studio and Flutter materials. Research findings suggest that applying the GBL model to the motor development of 12th grade pupils can improve typing skills, training rigor, agility, and caution. The application of this model is very good because it invites students to learn while playing, which makes them feel happy because so much knowledge is acquired. In addition, the majority of Vocational High School students orientation after graduation is working, so they are more likely to do practice than theory. It can be concluded that the GBL model contributes positively to the motor development of 12th grade RPL Vocational High School students in Surakarta.